1996
DOI: 10.1073/pnas.93.20.10589
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional regulation of vascular endothelial growth factor mRNA by the product of the VHL tumor suppressor gene.

Abstract: The (15)(16)(17). These factors include acidic fibroblast growth factor, basic fibroblast growth factor (bFGF), epidermal growth factor, transforming growth factors a and 13, tumor necrosis factor a, and vascular endothelial growth factor (VEGF). VEGF is secreted by a number of tumors and is normally expressed in the kidney, brain, and other tissues (18-22).VEGF is also markedly elevated in both VHL-associated and sporadic central nervous system hemangioblastomas (23, 24) and renal carcinomas (25,26). In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
290
3
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 479 publications
(306 citation statements)
references
References 36 publications
10
290
3
3
Order By: Relevance
“…One possibility could be that both HPVencoded oncoproteins, E6 and E7, impact VEGF expression and do so, not only by stimulating the activity of the promoter, but also by a ecting mRNA stability. Indeed, other oncogenes as well as the VHL tumor suppressor gene (Gnarra et al, 1996;Levy et al, 1996) have been found to increase the stability of VEGF mRNA. Additionally, other genetic changes present in the cervical cancer cells tested in the present study, may also have a positive impact on the overall level of VEGF expression.…”
Section: Hpv-16 E6 Oncoprotein and Vegf In Tumor Angiogenesismentioning
confidence: 99%
“…One possibility could be that both HPVencoded oncoproteins, E6 and E7, impact VEGF expression and do so, not only by stimulating the activity of the promoter, but also by a ecting mRNA stability. Indeed, other oncogenes as well as the VHL tumor suppressor gene (Gnarra et al, 1996;Levy et al, 1996) have been found to increase the stability of VEGF mRNA. Additionally, other genetic changes present in the cervical cancer cells tested in the present study, may also have a positive impact on the overall level of VEGF expression.…”
Section: Hpv-16 E6 Oncoprotein and Vegf In Tumor Angiogenesismentioning
confidence: 99%
“…Although the molecular function of the VHL gene product, pVHL, was initially not known when it was first identified by positional cloning in 1993, 3 observations that oxygen-dependent regulation of hypoxia-inducible genes was lost in VHL-deficient cell lines suggested a role for pVHL in oxygen sensing. [4][5][6] In a seminal paper, Maxwell et al 7 showed that pVHL was critical for targeting the a-subunit of hypoxia-inducible factor (HIF) for oxygen-dependent proteolysis, thus providing a direct molecular link between VHLassociated tumorigenesis and oxygen sensing via HIF. HIFs belong to the PAS (Per-arylhydrocarbon receptor nuclear translocator (ARNT)-Sim) family of basic helix-loop-helix (bHLH) transcription factors and bind DNA as heterodimers.…”
mentioning
confidence: 99%
“…Loss of heterozygosity at the VHL gene locus has been described for premalignant lesions of the kidney, such as atypical cysts (32,49), suggesting that inactivation of the VHL gene is an early event in renal carcinogenesis. Furthermore, reintroduction of a wild-type but not mutant VHL cDNA into VHL (Ϫ/Ϫ) renal carcinoma cells suppresses their ability to form tumors in nude mouse xenograft assays (11,18).…”
mentioning
confidence: 99%